Evaluation Of Medicine Logistics Management In Pharmacy Installations - Ginting, Rosita; Simanjuntak, Mahdalena; ., Irmayani; Br Ginting, Luci Riani (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Puskesmas is a primary health care facility that focuses on promotive and preventive efforts. In carrying out its duties to serve the community, community health centers carry out drug management which includes pharmaceutical, health and laboratory services. Drug logistics management is a series of activities that include planning, procurement, storage, distribution and optimal destruction of drugs. Objective: This study aims to evaluate drug logistics management at the Lubuk Pakam Community Health Center pharmacy installation. Method: The research uses a qualitative approach with in-depth interview methods. Results: The results showed that drug planning was based on use in the previous year and existing disease patterns. Medicines are procured every two months using the LPLPO form, while medicines are received by matching the medicines received with the invoice. The drugs received are stored using the FIFO, FEFO method, and are arranged alphabetically. Distribution of medicines from Puskesmas is carried out to sub-district health centers and Poskedes. Expired medicines are destroyed by collecting and recording expired medicines before they are sent to the Health Service pharmacy installation. In general, drug logistics management is running quite well, although drug procurement is still done manually. Suggestion: Researchers suggest that Community Health Centers can improve drug logistics management to become more efficient.